2021
DOI: 10.1115/1.4049155
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of Liquid Shock Absorption for Prevention of Traumatic Brain Injury

Abstract: Mild traumatic brain injury (mTBI), more colloquially known as concussion, is common in contact sports such as American football, leading to increased scrutiny of head protective gear. Standardized laboratory impact testing, such as the yearly NFL helmet test, is used to rank the protective performance of football helmets, motivating new technologies to improve the safety of helmets relative to existing equipment. In this work, we hypothesized that a helmet which transmits a nearly constant minimum force will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In a recent biomechanical analysis of football helmets, Alizadeh et al discussed how ideal energy-dissipating materials would adjust their properties to maximize the stroke under all impact conditions. [7] Their study showed that under theoretically ideal conditions, concussions may be reduced by 73%. [7] The high rate-dependence and soft-elastic behavior of liquid-crystal materials may provide a means to help approach these ideal impact conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent biomechanical analysis of football helmets, Alizadeh et al discussed how ideal energy-dissipating materials would adjust their properties to maximize the stroke under all impact conditions. [7] Their study showed that under theoretically ideal conditions, concussions may be reduced by 73%. [7] The high rate-dependence and soft-elastic behavior of liquid-crystal materials may provide a means to help approach these ideal impact conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Their study showed that under theoretically ideal conditions, concussions may be reduced by 73%. [7] The high rate-dependence and soft-elastic behavior of liquid-crystal materials may provide a means to help approach these ideal impact conditions. When designing personal safety equipment or protective features for machines and electronics, it makes more sense to use a durable material that will be able to maximize energy dissipation while minimizing peak stresses across a range of loading conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible explanations may be: (i) the laboratory impacts were generally simulated for the research of head impacts in football matches, which may explain the similarity between laboratory impacts and college football impacts; (ii) the MMA head impacts and NHTSA car crash dummy head impacts were measured without protective helmets, while the college football head impacts and the NASCAR head impacts were measured with protective helmets that protect the players/drivers from concussion. The helmet can effectively change the impact response of the head [51], which may explain the similarity between MMA impacts and NHTSA impacts, as well as among NASCAR impacts, college football impacts and laboratory impacts.…”
Section: Discussionmentioning
confidence: 99%
“…An ideal shock absorber exerts a near-constant force over its full stroke length to absorb the energy of an impact (Baumeister et al, 1997;Fanton et al, 2020;Spinelli et al, 2018;Vahid Alizadeh et al, 2021). The necessary constant force level is inversely proportional to the usable stroke length; a longer stroke length allows the shock absorber to spread the force out over a longer displacement, allowing for a lower force level.…”
Section: Introductionmentioning
confidence: 99%